2020
DOI: 10.3389/fmicb.2020.594265
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Earthworms on Fungal Diversity and Community Structure in Farmland Soil With Returned Straw

Abstract: BackgroundTo promote the decomposition of returned straw, reduce the incidence of soil-borne diseases caused by returned straw, and accelerate the conversion of straw carbon into soil carbon, we inoculated earthworms into fields with returned straw. The earthworms accelerated straw degradation and promoted carbon conversion. However, the impact of externally inoculated earthworms on the farmland soil ecosystem, especially the structure and the function of its microbial community, remains unclear.MethodsWe anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…This is in line with previous reports that found that Zopfiella was particularly present during vermicomposting (Neher et al, 2013). In contrast, Zopfiella was found to account for up to 5% of the relative abundance of fungi in control farmland soils, which was significantly higher than in the same soils treated with earthworms (Song et al, 2020). Some Zopfiella species produce zopfiellin, a secondary metabolite with antifungal properties (Futagawa et al, 2002), that could be involved in soil pathogen suppression (Liu et al, 2019) in some soils, and might have indirectly affected the fungal community in our experiment, explaining indirectly some of the SFWC effect on fungal communities.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous reports that found that Zopfiella was particularly present during vermicomposting (Neher et al, 2013). In contrast, Zopfiella was found to account for up to 5% of the relative abundance of fungi in control farmland soils, which was significantly higher than in the same soils treated with earthworms (Song et al, 2020). Some Zopfiella species produce zopfiellin, a secondary metabolite with antifungal properties (Futagawa et al, 2002), that could be involved in soil pathogen suppression (Liu et al, 2019) in some soils, and might have indirectly affected the fungal community in our experiment, explaining indirectly some of the SFWC effect on fungal communities.…”
Section: Discussionsupporting
confidence: 92%
“…Zopfiella was more abundant in our pots containing collembolans and earthworms, in line with its dominance during vermicomposting [ 78 ]. In contrast, Zopfiella was less abundant in the absence of earthworms in a farmland soils [ 79 ]. Some Zopfiella species produce zopfiellin, a secondary metabolite with antifungal properties [ 80 ], that could be involved in soil pathogen suppression [ 81 ], and might have indirectly affected the fungal community in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the bacteria in this phylum can produce indole acetic acid and ammonia, which can also fix N 2 , all these properties of actinobacteria would promote tobacco growth ( Laassami et al, 2020 ). For the fungal community, unclassified_k_fungi with strong cellulose dissolution ability was present in the samples ( Song et al, 2020 ). As mentioned above, these shared microorganisms in the samples, such as Mortierellomycota, have been reported as effective organic matter transformers ( Santillán et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%